BENTUK PELAYANAN UNGGULAN BADAN USAHA MILIK MADRASAH (BUMM) SEBAGAI STRATEGI BRANDING SCHOOL - Siti Nurjanah; Sabar Narimo; Djalal Fuadi; Minsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the form of superior services of Madrasah-Owned Enterprises (BUMM) as a school branding strategy. This qualitative research was conducted at MI Muhammadiyah Karanganyar. The subjects were the madrasah head and teachers. Data were collected through observation, interviews, and documentation. The research subjects were the madrasah head and teachers, the validity of the data with triangulation of techniques and sources. Data were analyzed through the Miles and Huberman model, namely reduction, presentation, and conclusion drawing. The results showed that the form of superior services managed by Madrasah-Owned Enterprises (BUMM) include: catering services that provide healthy and hygienic food, madrasah stores support the learning and operational needs of madrasah residents, and shuttle services ensure student comfort and safety. These three services not only serve to meet the needs of the madrasah community, but also become an effective school branding strategy to strengthen the image of the madrasah as a caring, innovative and quality educational institution. This research is still limited to exploring the form of excellent services, so further studies are needed to explore their implementation and impact, as well as challenges and solutions to their management.